2013
DOI: 10.1007/s10905-013-9420-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraspecific Competition and Host-Parasitoid Developmental Timing on Foraging Behaviour of a Parasitoid Wasp

Abstract: In a context where hosts are distributed in patches and susceptible to parasitism for a limited time, female parasitoids foraging for hosts might experience intraspecific competition. We investigated the effects of host and parasitoid developmental stage and intraspecific competition among foraging females on host-searching behaviour in the parasitoid wasp Hyposoter horticola. We found that H. horticola females have a pre-reproductive adult stage during which their eggs are not mature yet and they forage very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 67 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…Differences in competition may explain the strong difference between the foraging strategies of the parasitoid and the hyperparasitoid. The adult female parasitoid experiences both interspecific competition [59] and very strong intraspecific competition for hosts [21,60], which leads to the behaviour of monitoring of potential host patches by multiple individuals over weeks [61]. This may drive them to disperse widely during egg laying.…”
Section: Results (A) Genetic Diversity Of the Hyperparasitoidmentioning
confidence: 99%
“…Differences in competition may explain the strong difference between the foraging strategies of the parasitoid and the hyperparasitoid. The adult female parasitoid experiences both interspecific competition [59] and very strong intraspecific competition for hosts [21,60], which leads to the behaviour of monitoring of potential host patches by multiple individuals over weeks [61]. This may drive them to disperse widely during egg laying.…”
Section: Results (A) Genetic Diversity Of the Hyperparasitoidmentioning
confidence: 99%
“…Melitaea cinxia egg clusters contain only about 150 eggs (Saastamoinen, 2007). Couchoux and van Nouhuys (2014) found that female H. horticola containx = 550 (±173 SD) mature eggs in their oviducts under laboratory conditions. Because H. horticola is synovigenic, it is likely to mature new eggs to replace those that are used (Jervis et al, 2001).…”
Section: Species Specific Biological Constraint: Wasp Egg Limitationmentioning
confidence: 91%
“…Most individuals successfully parasitize significantly fewer hosts than they have eggs, and egg limitation cannot dictate the average foraging behavior. Additionally, if host egg clusters differed in quality and wasps were choosey, then the rate of parasitism is predicted to vary greatly from cluster to cluster, which it does not, even with respect to egg cluster size (van Nouhuys and Ehrnsten, 2004;Couchoux and van Nouhuys, 2014).…”
Section: Species Specific Biological Constraint: Wasp Egg Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fruit fly Drosophila melanogaster and parasitoid wasp Hyposoter horticola , behavioral plasticity was also identified [1920]. Similarly, the black bean aphid ( Aphis fabae ) showed high plasticity in host choice behaviors [13].…”
Section: Introductionmentioning
confidence: 99%